KAJIAN DINAMIKA PERATURAN DAN KEBIJAKAN PENATAAN RUANG TERHADAP MUATAN PERATURAN DAERAH TENTANG RENCANA TATA RUANG WILAYAH KABUPATEN NIAS BARAT - Gulo, Analisis; Mendoza, Mhd Dominique; Pangaribuan, Wanapri (Universitas Negeri Medan, 2024)
The implementation of spatial use, the dynamics of development as well as the development of the strategic environment in recent years, have often influenced the implementation of the West Nias RTRW as a reference in development. This sometimes causes an imbalance in the arrangement of a space or region. This paper aims to review the suitability of the content of the West Nias RTRW with regulations and policies related to spatial planning. Based on the results of the study, it is concluded that it is necessary to renew the technical material for the RTRW of West Nias Regency by adjusting the dynamics of the latest spatial planning regulations and policies. It is also hoped that there will be serious attention from the local government regarding the sustainability of funding to the stage of stipulation of the Regional Regulation on the revision of the RTRW, as well as the placement of human resources with a spatial planning background in technical OPD.Keywords: spatial planning, RTRW revision, West Nias Regency